Comparison of Rice N Uptake in Paddies with Different Organic Carbon - VASEGHI*, S.; VALYNEJAD†, M.; FALLAH‡, V.M.; PAZIRA†, E.; FALLAH‡, A.; MOAMENI‡, A. (Asian Journal of Chemistry, 2024)
Efficient use of all inputs is vital to achieve and sustain high cropyields, maintain resource quality and minimize environmental pollution.Fertilizer N is one of the major inputs in rice production. Blanket fertilizerrecommendations do not take into account the high field-to-field variabilityand within-season dynamic changes in indigenous N supply.Since the plant growth reflects the total N supply from all sources, plantN status will be a good indicator of N availability to crops at any giventime. Leaf colour chart (LCC) is simple portable diagnostic tool, todetermine the timing of N top dressing. We used it to test need-basedN-management approaches for rice (Oryza sativa L.) and comparedLCC with split three rates (45, 90 and 135) and three timing at twosites, in northern Iran. Grain yield, yield attributes, total N uptake andfertilizer-N use efficiency were measured. All treatments showed significantgrain yield increase relative to zero-N control. Yield loss wasobserved when split 135 timing was used in both sites due to lodgingand pest damage. Grain yield of LCC treatments were higher than splittreatments. The grain yield of zero-N control in site 2 was 18.5 % higherthan that of site 1 due to higher soil organic matter percent. LCC 5treatment had higher AE than LCC 4 and fixed - 135 at the less N rate.As a result LCC treatments indicated that N management based on LCCshade 5 helped avoid over application of N to rice.